An Fc Gamma Receptor-Mediated Upregulation of the Production of Interleukin 10 by Intravenous Immunoglobulin in Bone-Marrow-Derived Mouse Dendritic Cells Stimulated with Lipopolysaccharide In Vitro. (18th June 2013) - Fujii, Akihiro; Kase, Yuko; Suzuki, Chiaki; Kamizono, Akihito; Imada, Teruaki
Abstract : Intravenous immunoglobulin (IVIG), a highly purified immunoglobulin fraction prepared from pooled plasma of several thousand donors, increased anti-inflammatory cytokine IL-10 production, while decreased proinflammatory cytokine IL-12p70 production in bone-marrow-derived mouse dendritic cells (BMDCs) stimulated with lipopolysaccharide (LPS). The changes of cytokine production were confirmed with the transcription levels of these cytokines. To study the mechanisms of this bidirectional effect, we investigated changes of intracellular molecules in the LPS-induced signaling pathway and observed that IVIG upregulated ERK1/2 phosphorylation while downregulated p38 MAPK phosphorylation. Using chemical inhibitors specific to protein kinases involved in activation of Fc gamma receptors (Fcγ Rs), which mediate IgG signals, we found that hyperphosphorylation of ERK1/2 and Syk phosphorylation occurred after stimulation of BMDC with LPS and IVIG, and the increasing effect on IL-10 production was abolished by these inhibitors. Furthermore, an antibody specific to Fcγ RI, one of Fcγ Rs involved in immune activation, inhibited IVIG-induced increases in IL-10 production, but not IL-12p70 decreases, whereas the anti-IL-10 antibody restored the decrease in IL-12p70 induced by IVIG. These findings suggest that IVIG induced the upregulation of IL-10 production through Fcγ RI activation, and IL-10 was indispensable to the suppressing effect of IVIG on the production of IL-12p70 in LPS-stimulated BMDC.